THE IMPACT OF PROFESSIONAL DEFORMATION AND FAMILY PSYCHOLOGY ON MORAL AND MORAL IMMUNITY IN PRIMARY TEACHERS (Universal International Scientific Journal, 2026)
This article examines the psychological characteristics of professional deformation in primary school teachers, their impact on their professional and personal activities, and important aspects of the formation of spiritual and moral immunity through family psychology. The results of the study show that family support and the development of moral values ​​are effective tools for reducing professional stress in teachers and increasing their child-rearing and social awareness.
Keywords: Primary school teachers, professional deformation, psychological characteristics, family psychology, spiritual and moral immunity.